Influência do modo de aplicação dp fluido de corte sobre a usinabilidade do aço ABNT 4340 no torneamento - Christiane Lacerda Soares (2016)
Manufacturing processes have become imperative tools regarding the evolution of the modern man. Among manufacturing processes, applied specially to metals, machining is featured for its versatility and great industrial applicability. Seeking the better understanding of the phenomena induced by the variation in operational inputs (cuttingspeed, feed rate, depth of cut and cutting fluid) cause in outputs (cutting temperature, roughness, chip forms, cutting force and specific energy), in this study AISI 4340 steel was investigated. Initially, a 32 full factorial experimental design was used for statistical analysis besides other configurations for the remaining analysis, in a total of 48 test runs. The results point out that the lowest temperatures were achieved by the use offlood cooling, followed by minimum quantity of fluid (MQF) and dry turning. Regarding surface roughness, feed rate showed itself as the most influent parameter and cutting fluid, regardless the application means, did not bring substantial benefits to this aspect. Chip analysis showed that the highest levels of feed rate and depth of cut generated shortest chips. Cutting force analysis led to the conclusion that cutting fluid is negligible for the results. Cutting force variation was given, in a significant way, by cutting speed, feed rate and depth of cut. One last evaluation concerns specific energy, in which it could be proved the lowest cutting resistance given by dry cut, followed by MQL and the worst result was given by flood cooling